2018
DOI: 10.1016/j.jpsychores.2017.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Psychobiological stress in vital exhaustion. Findings from the Men Stress 40 + study

Abstract: Signs of allostatic load are detectable in vitally exhausted men at a stage where no major cardiovascular consequences have yet ensued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
2
15
0
Order By: Relevance
“…Despite significant additional increases in cortisol, speaking standard German did not lead to higher levels of self-reported stress or anxiety during the TSST. This observation of a dissociation between psychological and biological markers of the stress response is not novel (e.g., Campbell & Ehlert, 2012;Noser, Fischer, Ruppen, & Ehlert, 2018). In the present context, these results may indicate that subjects were unaware that speaking standard German was stressful to them, which again is in line with standard German being taught from an early age onwards as one of two varieties of German that are being spoken in Switzerland.…”
Section: Discussionsupporting
confidence: 64%
“…Despite significant additional increases in cortisol, speaking standard German did not lead to higher levels of self-reported stress or anxiety during the TSST. This observation of a dissociation between psychological and biological markers of the stress response is not novel (e.g., Campbell & Ehlert, 2012;Noser, Fischer, Ruppen, & Ehlert, 2018). In the present context, these results may indicate that subjects were unaware that speaking standard German was stressful to them, which again is in line with standard German being taught from an early age onwards as one of two varieties of German that are being spoken in Switzerland.…”
Section: Discussionsupporting
confidence: 64%
“…Data were collected in the framework of the Men Stress 40+ Study, a large research project investigating the effects of stress in men aged 40–75 years (Noser et al, 2018 ). Participants were recruited in the German-speaking part of Switzerland between January and September 2016 through flier distribution, newspaper announcements, mailing lists, and online advertisements.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, low social support is considered to be stressful and detrimental for an individual's well-being. In one study, men with severe VE reported the lowest levels of social support (Noser et al, 2018 ). Likewise, low perceived support from others was found to contribute to VE and heart failure (Cené et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the following, only procedures and measures used for the present study are described. For more detailed information about the project, see Noser, Fischer, Ruppen, and Ehlert [ 36 ].…”
Section: Methodsmentioning
confidence: 99%